Ru/Al2O3 catalyzed CO2 hydrogenation : oxygen-exchange on metal-support interfaces - Yan, Yong (2020)
The metal-support interfaces of metallic nanoparticles supported on oxide surfaces determine the activated dissociation of CO2 in CO2 hydrogenation. It also guides the catalytic pathway towards either CO2 methanation or reverse water-gas shift (rWGS). In this work, Ru/Al2O3 catalysts with different Ru structural configurations were prepared by controlling the Ru weight loadings, which revealed the structure-dependence of production rates for CO and CH4 formation with different apparent activation energies. Based on the characterization results, two catalyst models were setup: the Ru9/Al2O3 model consisted of an interface of monolayer Ru sites tightly contacted with γ-Al2O3 support, and the Ru35/Al2O3 model represented a relatively larger Ru nanocluster supported on γ-Al2O3. Theoretical calculations of these two models demonstrated that monolayer Ru sites favored the rWGS route with a relatively low energy barrier for both CO2 activation and CO formation steps, while Ru nanoclusters preferred the methanation route energetically. Furthermore, the combination of theoretical calculations and experimental isotope-exchange measurements suggested that the interfacial O species in Ru-O-Al interfaces played a critical role in CO2 activation via oxygen-exchanging with the O atom in the feeding CO2 and consequently incorporation into the final hydrogenation product.